X-RAY CT IMAGING APPARATUS AND IMAGE PROCESSING METHOD THEREFOR - HIRASAWA YUTA; TAKADA YUYA (2013)
PROBLEM TO BE SOLVED: To provide an X-ray CT imaging apparatus capable of acquiring images desired by a user in reconstructing an image acquired from the CT apparatus without requiring complicated processing.SOLUTION: The CT imaging apparatus includes: an X-ray irradiation section for irradiating a subject with an X-ray; an X-ray detecting section for outputting the digital amount of electric signals corresponding to the incident X-ray at a constant frame rate; a turning means for moving the pair of the X-ray irradiation section and the X-ray detecting section around the subject so that they are opposed to each other with the subject interposed; a storage means for sequentially storing, as projected image data, image signals to be output by the detecting means when the turning means moves the X-ray irradiation section and the X-ray detecting section around the subject; and an image processing means for acquiring image reconstruction computation on the basis of the projected image data stored in the storage means. For the projected image data, the image processing means uses a filter having a threshold set therein to emphasize a high-frequency component up to the threshold, and performs reconstruction computation for the image data.